Visualization and Data Analysis 2012 2012
DOI: 10.1117/12.908288
|View full text |Cite
|
Sign up to set email alerts
|

Comparative visualization of ensembles using ensemble surface slicing

Abstract: By definition, an ensemble is a set of surfaces or volumes derived from a series of simulations or experiments. Sometimes the series is run with different initial conditions for one parameter to determine parameter sensitivity. The understanding and identification of visual similarities and differences among the shapes of members of an ensemble is an acute and growing challenge for researchers across the physical sciences. More specifically, the task of gaining spatial understanding and identifying similaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…A sample image of their technique is shown in Figure 2. In three dimensions, slicing can help create an impression of di↵erences in isosurfaces, as demonstrated by Alabi et al [1] and shown in Figure 3. As you can see, even simple tasks such as rendering spaghetti plots becomes a visualization challenge in three dimensions.…”
Section: Visualization Of Ensemble Datamentioning
confidence: 93%
“…A sample image of their technique is shown in Figure 2. In three dimensions, slicing can help create an impression of di↵erences in isosurfaces, as demonstrated by Alabi et al [1] and shown in Figure 3. As you can see, even simple tasks such as rendering spaghetti plots becomes a visualization challenge in three dimensions.…”
Section: Visualization Of Ensemble Datamentioning
confidence: 93%
“…Several methods have been proposed to visualize isosurfaces extracted from 3D ensemble data, e.g., by means of animation [6], volume rendering [11,44], or confidence envelopes [35,37,48]. Other methods aim at rendering multiple isosurfaces into a single 3D view [1,8]. However, only a few ensemble members can be visualized simultaneously due to cluttering and occlusion.…”
Section: Related Workmentioning
confidence: 98%
“…On the other hand, ensemble space visual analytic tools have been developed with different levels of complexity. The least complex tool shows a side‐by‐side comparison of 3D surfaces [AWH*12]. Increasing in complexity, we see the use of pairwise sequential animation and screen door tinting to show the differences between ensemble members using value changes to field points [PPA*12], the comparison of 2D function ensembles on three levels of details (i.e.…”
Section: Related Workmentioning
confidence: 99%